Understanding Demotivating Factors on EFL Students in Online Learning - Siti Maemunah; Sidik Indra Nugraha; Acep Bahrum Kamil (Universitas Muhammadiyah Enrekang, 2021)
Demotivation is a complex problem that many foreign language (FL) learners faced, and it is caused by a variety of factors including the teacher, poor self-esteem, and previous bad language learning experiences(BABA KHOUYA, 2018). This study aimed to understand the demotivating factors on EFL students in online learning. The participants of this study were three students of the third grade of senior high school in Karawang. This study used a qualitative case study design to address the research objectives. The data for this study was gathered through semi-structured interview questions as an instrument of this study. The collecting data was obtained through Google meeting. The result of this study revealed that there are two demotivating factors on EFL students in online learning. Those are the teacher’s methods and learning material. In this case, the researcher found out that those factors are from the external factors. In the teacher’s method, there are two aspects that demotivate EFL students in online learning. The first aspect is because the teacher always speaks English all the time during learning. The second is because the teacher did not evaluate the students’ assignments. The last factor is the learning materials, the students get difficult to understand the materials during online learning. Keywords: demotivation factors, online learning.